Energy Analysis of Evaporator System in Fertilizer Production - Ingebrigtsen, Vegard Byre (Institutt for energi- og prosessteknikk, 2012)
Yara Glomfjord is the north most production facility of compound fertilizer in the world and produces annually about 500 000 tons NPK and 200 000 tons CN. The general energy system of the process plant utilizes steam as the main energy carrier for the entire production site. Yara Glomfjord has today a general lack of steam, and steam is produced in EGA boilers approximately 75% of operational time to cover all heating tasks. The main objective of this Master thesis is to analyze energy flow in in the factory to identify energy saving potential, and later to suggest improvements for the CN-evaporator system in order to retire the use of EGA boilers and supply excess heat for other heating tasks in the factory.First off analysis was made on general energy flows in the factory. This was done in order to reveal potential for energy savings and to clarify which paths to choose for further heat integration. The result of the analysis shows that latent heat flows are of far greater importance than sensible heat flows to the general steam balance at Yara Glomfjord. It was also identified that the large potential for latent heat recovery lies within the evaporator equipment.Next up this text suggests investment in evaporator equipment in order to integrate latent heat, so that the overall steam consumption goes down. Three different suggestions were presented and analyzed in detail in the document: CN-Evaporator System Design. The most proving suggestions are new equipment coupled in cascade with old evaporators or a new independent MVR evaporator in front of old solution. Both suggestions are found to retire EGA boilers completely and also supply excess heat for other heating tasks. This text recommends one of these two suggestions.To suggest new improvements in the CN-evaporator system Epcon Evaporation Technology AS were involved. Testing at Epcon s facilities in Trondheim indicate a new possibility. For the suggested retrofit cascade evaporation system, submergence of boiling pressure is possible. These findings ...